Database and software for the analysis of mutations at the human p53 gene. - Cariello, N F (1994)
A computerized database containing DNA sequence information regarding human p53 mutants has been created. The database itself is in the dBASE format and contains information on nearly 3000 mutants. In addition, an IBM PC compatible software package to analyze the information in the database has been developed. Both the database and software are freely available via the Internet.